Challenges faced and coping strategies used by Malaysian International Medical Graduates surviving internships: A Qualitative Study - Syuhada Hamzah; Aizuddin A. N.; Sharifa Ezat Wan Puteh; Siti Rahayu Mat Husin; Mohamed Shazwan Zailani; Abdul Aziz Harith (PLoS ONE, 2025)
Background Malaysian International Medical Graduates (MIMGs) faced unique challenges during their medical internships in Malaysia, impacting their training experience and overall well-being. This study aims to explore these challenges and identify the coping strategies MIMGs employ to navigate their internships successfully. By understanding these factors, the study seeks to provide insights for improving the internship experience and reducing attrition rates among MIMGs. Methods A qualitative research design was employed, utilising in-depth interviews with eleven MIMGs to gather detailed insights into their internship experiences. Thematic analysis was used to identify and analyse common themes and subthemes related to individual, training system, and working environment challenges and the strategies employed to cope with these challenges. Findings The study identified three main themes, eight subthemes of challenges faced by MIMGs, and thirteen subthemes for coping strategies to survive an internship. The themes are individual challenges, training system issues, and working environment difficulties. Individual challenges included high levels of stress and burnout due to long working hours, heavy patient loads, and emotional tolls. Training system issues encompassed bureaucratic hurdles, inadequate infrastructure, and low financial incentives. The challenges of the working environment involved difficulties with cultural adaptation, hierarchical structures, and language barriers. MIMGs employed various coping strategies, with peer support emerging as a powerful tool, along with resilience, self-care practices, and proactive communication. Conclusion This study provides valuable insights into the challenges and coping strategies of MIMGs during their internships in Malaysia. The results suggest that targeted interventions and systemic changes are necessary to support MIMGs effectively and enhance their training experience. Future research should explore these issues further, with larger samples and in different contexts, to develop comprehensive strategies for improving medical internships globally.